Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan (Studi Di Divisi Account Executive PT Agrodana Futures) - Rijanto, Alfitri; Mukaram (Jurnal Riset Bisnis dan Investasi, 2018)
This research is to know the influence of organizational culture on employee performance division of account executive PT Agrodana Futures. PT Agrodana Futures is a futures trading company specializing in foreign exchange trading of Asian stock indices. The influencing variables are the organizational culture with dimensions that refer to Cameron and Quinn (2006) ie clan, adhocracy, market, and hierarchy. While the variables that are influenced is the performance of employees with dimensions that refer to the Dharma (2003) namely the quality of work, the quantity of work, and timeliness. The method of this research is descriptive quantitative by using nonprobability sampling technique that is saturated sampling. The results showed that organizational culture has a mean value of 4.444 and employee performance with a mean value of 4.3670 which means both are in the very good category. Meanwhile, the organizational culture of account executive division at PT Agrodana Futures gives 26.3% influence on employee performance.